COMPREHENSIVE REVIEW ON BIOMASS POTENTIAL FOR AGRICULTURAL BIOGAS PRODUCTION IN SRI LANKA - Charithangi, Piyaruwani (Journal on Processing and Energy in Agriculture, 2023)
Biogas emerges as a renewable energy option that offers a wide range of advantages. This study assesses the appropriateness of a range of biomass feedstock choices, encompassing energy crops, bio-waste, materials derived from both animals and plants, as well as organic residues produced within the food production sector. The aim is to determine their potential as viable substrates for agricultural biogas plants in Sri Lanka. Nevertheless, administrative obstacles and inefficiencies within the existing facilities impede the complete utilization of this potential. In parallel, it is of paramount importance to develop and enhance cost-effective technologies for converting agricultural biomass into energy, all while avoiding conflicts with the food and animal feed industries. Consideration should be given to judiciously utilizing disputed resources like fresh fruits and vegetables as raw materials. When employing biomass for energy generation, factors like economic viability, resource availability, and storage need to be meticulously assessed. Additionally, this review proposes that conducting a life cycle assessment within Sri Lanka's energy sector is both feasible and essential for comparing the energy potential of biomass-based sources with conventional fossil fuels. Such an evaluation can offer invaluable insights into sustainable energy choices for the nation's future.